FOOD, LAW & THE ENVIRONMENT: INFORMATIONAL AND STRUCTURAL CHANGES FOR A SUSTAINABLE FOOD SYSTEM (Utah Environmental Law Review; Vol 31 No 2 (2011), 2011)
Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;} There is growing interest in learning about the environmental impacts of our food choices, and in modifying individual behaviors and choices that have adverse ecological effects. "Integrating sustainable consumption and production principles into everyday patterns of behavior is a major policy challenge for governments seeking long-term sustainability, yet there is an acknowledged need for tools and instruments to put this into practice." In order to create a more sustainable food system, these tools must include information and structural change. As I've noted in my past work, law and public policy should increase available consumer information about the consequences of food choices, and, the focus of this Article, make structural changes in the food system that increases access and helps form a more sustainable food system. Information, through eco-labeling and food education programs, will help play a role in changing consumer preferences. And the knowledge gained through creating these informational tools, like environmental life-cycle analysis, will help "identify the most energy-draining stages of consumption." Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;}